2018
DOI: 10.1111/vde.12699
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant in the NSDHL gene in a cat with multiple congenital lesions resembling inflammatory linear verrucous epidermal nevi

Abstract: Background The feline counterpart of human inflammatory linear verrucous epidermal nevus (ILVEN) has been described; however, the possible underlying developmental defect has not been investigated. Objective To report a case of multiple ILVEN‐like lesions in a cat with a genetic variant in the NSDHL gene. Animals A 2‐year‐old, female, domestic short hair cat with a history of multiple alopecic, verrucous, hyperpigmented and erythematous skin lesions, following Blaschko's lines on the head, the limbs, the trunk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…As clinical and histopathological findings resembled previously published companion animals with congenital epidermal nevi [10][11][12], we hypothesized that the phenotype in the affected dog was due to a heterozygous variant in the NSDHL gene. Hence, NSDHL was investigated as the top functional candidate gene.…”
Section: Genetic Analysissupporting
confidence: 67%
See 3 more Smart Citations
“…As clinical and histopathological findings resembled previously published companion animals with congenital epidermal nevi [10][11][12], we hypothesized that the phenotype in the affected dog was due to a heterozygous variant in the NSDHL gene. Hence, NSDHL was investigated as the top functional candidate gene.…”
Section: Genetic Analysissupporting
confidence: 67%
“…In this study, we identified a heterozygous NSDHL: c.718_722delGAACA frameshift variant in a mixed breed dog with a severe form of progressive epidermal nevi. The NSDHL gene encodes the enzyme NAD(P) dependent steroid dehydrogenase-like, which is involved in cholesterol biosynthesis and has been associated with human CHILD syndrome [8], as well as canine and feline congenital epidermal nevi [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 So far, only a limited number of X-linked genodermatoses characterized by cutaneous mosaicism have been recognized in domestic animals. [3][4][5][6][7] We have described an X-linked semidominant congenital cornification defect in a 7-month-old female Labrador retriever-cross dog showing cutaneous mosaicism. Alopecic scaly plaques following the Blaschko's lines on the limbs, the head, the dorsal neck and the trunk, and severe foot pads hyperkeratosis were the most relevant lesions (Figure 1a,b).…”
Section: Dear Editorsmentioning
confidence: 99%